2018
DOI: 10.1136/annrheumdis-2017-212794
|View full text |Cite
|
Sign up to set email alerts
|

TheSTAT4SLE risk allele rs7574865[T] is associated with increased IL-12-induced IFN-γ production in T cells from patients with SLE

Abstract: ObjectivesGenetic variants in the transcription factor STAT4 are associated with increased susceptibility to systemic lupus erythematosus (SLE) and a more severe disease phenotype. This study aimed to clarify how the SLE-associated intronic STAT4 risk allele rs7574865[T] affects the function of immune cells in SLE.MethodsPeripheral blood mononuclear cells (PBMCs) were isolated from 52 genotyped patients with SLE. Phosphorylation of STAT4 (pSTAT4) and STAT1 (pSTAT1) in response to interferon (IFN)-α, IFN-γ or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 46 publications
0
61
0
1
Order By: Relevance
“…Furthermore, eQTL variants can also indicate the direction of gene regulation (figure 3B). For example, upregulation of eQTL risk genes such as STAT4 60 and CCR6 61 has been linked to upregulated production of inflammatory cytokines in patients. As individual effects of eQTL variants are small, examining the overall effects of eQTL variants in the disease was attempted by combining the whole data sets from a GWAS and an eQTL study 62.…”
Section: What Can We Learn From Genetics Of Ra?mentioning
confidence: 99%
“…Furthermore, eQTL variants can also indicate the direction of gene regulation (figure 3B). For example, upregulation of eQTL risk genes such as STAT4 60 and CCR6 61 has been linked to upregulated production of inflammatory cytokines in patients. As individual effects of eQTL variants are small, examining the overall effects of eQTL variants in the disease was attempted by combining the whole data sets from a GWAS and an eQTL study 62.…”
Section: What Can We Learn From Genetics Of Ra?mentioning
confidence: 99%
“…The intronic SLE-associated STAT4 SNPs are linked to a disease phenotype with an earlier onset and an increased risk for stroke and nephritis with severe renal insufficiency 67–69. We recently showed that activated T cells from STAT4 risk allele carriers with SLE have increased levels of STAT4 protein, resulting in more phosphorylated STAT4 in response to IL-12 and IFN-α, and an augmented IL-12-induced IFN-γ production 70. In contrast, activated T cells from healthy individuals carrying the STAT4 risk allele displayed a decreased response.…”
Section: Introductionmentioning
confidence: 99%
“…A global transancestral association study of SLE using genomic data from more than 27 000 individuals, including 11 590 patients with SLE, confirmed that SLE risk has both ancestry-dependent and ancestry-independent contributors 50. Hagberg et al demonstrated increased T cell STAT4 responsiveness to interleukin (IL)-12 and IFN-α in patients with SLE carrying the STAT4 risk allele 51. Furthermore, healthy individuals with the risk gene variant have normal STAT4 responsiveness to IL-12, which can become ‘lupus like’ if cells from these individuals are exposed to IFN-α 52.…”
Section: Type I Ifns In Autoimmune Diseasesmentioning
confidence: 98%